2004
DOI: 10.1007/bf02432908
|View full text |Cite
|
Sign up to set email alerts
|

Rademacher chaos: tail estimates versus limit theorems

Abstract: We study Rademacher chaos indexed by a sparse set which has a fractional combinatorial dimension. We obtain tail estimates for finite sums and a normal limit theorem as the size tends to infinity. The tails for finite sums may be much larger than the tails of the limit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 19 publications
4
8
0
Order By: Relevance
“…In contrast to that, as we will see below, asymptotically the sums S N have the standard normal distribution, and thus the functions r  ,  ∈ A, are asymptotically independent like the usual Rademacher functions. This "divergence" in estimates for the moments of a Rademacher fractional chaos and its asymptotic behaviour was previously observed in the paper [14]. To justify the last assertion, we will use Theorem 1.7 from [14].…”
Section: Asymptotic Independence Of a Fractional Rademacher Chaossupporting
confidence: 58%
See 3 more Smart Citations
“…In contrast to that, as we will see below, asymptotically the sums S N have the standard normal distribution, and thus the functions r  ,  ∈ A, are asymptotically independent like the usual Rademacher functions. This "divergence" in estimates for the moments of a Rademacher fractional chaos and its asymptotic behaviour was previously observed in the paper [14]. To justify the last assertion, we will use Theorem 1.7 from [14].…”
Section: Asymptotic Independence Of a Fractional Rademacher Chaossupporting
confidence: 58%
“…This "divergence" in estimates for the moments of a Rademacher fractional chaos and its asymptotic behaviour was previously observed in the paper [14]. To justify the last assertion, we will use Theorem 1.7 from [14].…”
Section: Asymptotic Independence Of a Fractional Rademacher Chaossupporting
confidence: 58%
See 2 more Smart Citations
“…Note that the Rademacher system itself is an unconditional (and even symmetric with constant 1) basic sequence in any symmetric space (see for example, Proposition 2.2 in [2]). The next step in the study of the behaviour of the Rademacher chaos in symmetric spaces was made by the authors of the present paper by employing the important concept of combinatorial dimension developed earlier by Blei (see [10]- [14]). Namely, in [9] it was shown that the above results in [7] and [8] can be extended to a non-complete chaos…”
Section: § 1 Introductionmentioning
confidence: 99%